Pembuatan Phantom dari Gips Sebagai Pengganti Tulang Manusia dan Bahan Akrilik Sebagai Pengganti Soft Tissue - Muhammad Sofyan; Alpha Olivia Hidayati; Anita Nur Mayani (Journal of Health (JoH), 2017)
Background: Phantom is very important in radiodiagnostic teaching method, especially in the laboratory of radiography. Exposing object in making radiograph have to consider the amount of radiation which is received by the object. In addition, phantoms price are relatively expensive. To resolve this issue, researcher made phantom using gypsum as subtitute material for bone and acrylic for soft tissue. Objective: This research is done to know how to make a genu phantom using gypsum as subtitute material for bone and acrylic for soft tissue. Methods: Research methods are images draft, draft procedures, procedures of use and testing. Phantom testing is done by making radiograph using phantom genu and human genu as object and the the result is compared to know the equation between genu phantom and genu of the human object Results: The result of testing radiograph showed that phantom structure is almost similar to human bone structure, however there are no bone trabecular. While soft tissue between genu phantom and human genu are almost similar. Based on descriptive analysis of densitometry measurement between genu phantom and human genu evidently there are no differences. Conclusion: Gypsum can be used as subtitute material for bone and acrylic as subtitute material for soft tissue, however could not show bone trabecular.